AB0299 REAL-WORLD ASSESSMENT OF GP2015 (ETANERCEPT BIOSIMILAR, SDZ-ETN): AN INTERIM ANALYSIS OF DATA FROM THE SELF-INJECTION ASSESSMENT QUESTIONNAIRE IN PATIENTS WITH RHEUMATOID ARTHRITIS IN THE COMPACT STUDY. (2nd June 2020) - Kellner, H.; Askari, A.; Kupka, T.; Friccius-Quecke, H.; Furlan, F.; Hachaichi, S.; Schmalzing, M.
Abstract : Background: COMPACT is a non-interventional study to collect real-world evidence in European countries and Canada on effectiveness, safety and quality of life in rheumatoid arthritis (RA), ankylosing spondylitis or psoriatic arthritis patients (pts) treated with SDZ-ETN (GP2015), an approved etanercept biosimilar. The first effectiveness and safety data from the study have been reported earlier 1 . Objectives: This interim analysis assessed patient usage behaviour and feelings of self-administered injection in general and with the auto-injector device using the Self-Injection Assessment Questionnaire (SIAQ) at Week 12 in pts with RA. Methods: Pts aged ≥18 years for whom treatment with SDZ ETN were initiated are being enrolled. The SIAQ, a patient questionnaire validated for pts with RA, was developed to assess overall pt experience with subcutaneous self-injection 2 . It assesses the perceived self-confidence on self-injection, potential barriers, as well as satisfaction with self-injection via device before the first self-injection (PRE module) and after dosing (POST module). The POST module used in COMPACT includes 21 items grouped into six hypothetical domains: "feelings about injection", "self-image", "self-confidence", "injection-site reactions", "ease of use of self-injection device (SD), and "satisfaction with self-injection". Descriptive statistics were used to summarise SIAQ POST module data. The results for "ease of use of SD" domain are reported here. The "ease of use of SD" was rated by pts on a 6-point scale: 1 (very difficult) to 6 (very easy). Results: Of the 430 pts recruited, pts with RA represented the largest group (59.5%, n=256). Majority of pts with RA (77.7%) had comorbidities. Of the 256 pts with RA, 102 (40%) pts who used SD responded to the questionnaire. Majority of the pts found usage of the SD easy or very easy, for each of the domains assessed (Table). 49 % and 14% of the patients were "comfortable" and "very comfortable", respectively using the SD. A majority of patients reported to be bothered by pain at the injection site "not at all" or only "a little" (69.6%), and to be bothered by redness "not at all" or only "a little" (89.2%), respectively. Conclusion: The interim analysis results, although descriptive, show a clear trend for ease of use and good satisfaction with SDZ-ETN SD in pts with RA. References: [1]Schmalzing M, et al. Arthritis Rheumatol . 2019;71 (suppl 10). [2]Keininger D, et al. Health Qual Life Outcomes . 2011, 13;9:2. Disclosure of Interests: Herbert Kellner: None declared, Ayman Askari Speakers bureau: Eli Lilly, Pfizer, Thomas Kupka: None declared, Hilke Friccius-Quecke Employee of: Sandoz Hexal AG, Fabricio Furlan Employee of: Sandoz Hexal AG, Sohaib HACHAICHI Employee of: Sandoz Hexal AG, Marc Schmalzing Consultant of: Paid consultant for Hexal AG